Social Environmental Eeterminants and Health: Rural Brazil versus Brazil Urban. - Rackynelly Alves SARMENTO; Ronei Marcos MORAES; Rodrigo Toledo Pinheiro de VIANA; Vanira Matos PESSOA; Fernando Ferreira CARNEIRO (Universidade de Brasília, 2015)
The rural population lives in socioeconomic inequality conditions motivated by several problems, including an insufficient sewage systems and water supply, these, sometimes, most responsibles by the appearance of waterborne diseases that contribute to the rise of child mortality and other problems. Rural areas in Brazil are defined by opposition and exclusion in urban areas. This definition is arbitrary and physical-geographic, not considering the social and economic processes involving the territories. This study purposed to verify, by means of sociodemographic aspects, environmental sanitation and main grievances/diseases importance for public health of the population from forest field and water, if the most rural municipalities (MMR) are more precarious than the more urban (MMU). To this end, was carried out a descriptive study based on secondary sources (Atlas of Human Development in Brazil, IBGE census, PNAD and Sinan). Among the results, it follows that the rural population identified by IBGE boils down to 15.6% of Brazil's population. In 29% of the municipalities, the population living in rural areas exceeds the city. The higher frequencies from IDMH very low are for MMR, while the higher frequency from IDMH very high and high are for MMU. In health, the MMR also exhibit deficiency. It was observed high incidence rates of diseases related to poor conditions of sanitation. From these results, it was identified a more precarious health profile in MMR when compared to MMU.